Stability of cylindrical shells subjected to axial compression and outside lateral pression - Dung, Dao Van (Vietnam Journal of Mechanics, 1993)
The method for calculating critical forces of cylindrical shells subjected to axial compression and outside lateral press ion has been presented. A numerical comparison based on the theory of least plastic processes, the simple loading process theory and the theory of elasticity for this problem was given.